Tunability in Crystallinity and Magnetic Properties of Core–Shell Fe Nanoparticles. (11th May 2014) - Singh, Gurvinder; Kumar, Puri Anil; Lundgren, Christopher; van Helvoort, Antonius T. J.; Mathieu, Roland; Wahlström, Erik; Glomm, Wilhelm R.
<x xml:space="preserve">Abstract</x> Monodisperse iron nanoparticles of size range 5–19 nm with controlled crystallinity and magnetic properties are synthesized via thermal decomposition of iron pentacarbonyl in the presence of an appropriate ligand. Crystalline body‐centered cubic iron nanoparticles synthesized in the presence of didodecyldimethylammonium bromide exhibit a high saturation magnetization and room temperature ferromagnetic behavior with a remarkable increased stability in the aqueous phase in comparison to amorphous nanoparticles synthesized in the presence of other ligands. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>